THE USE OF ESA (ENGAGE, STUDY, ACTIVATE) METHOD IN IMPROVING STUDENTS’ VOCABULARY MASTERY OF EIGHT GRADE AT SMP NEGERI 9 BAUBAU - Mayun Sarita; Esa Penilta Amiruddin (English Education Journal, 2021)
The aim of this study was to find out whether there is any significant effect of using ESA method in improving students’ vocabulary of eight grade students at SMP Negeri 9 Baubau. The instrument of the research was test (pre-test and post-test). The study lasted eight sessions, with one meeting serving as a pre-test, six meetings as treatment, and one meeting serving as a post-test. In analyzing the data, the researchers applied descriptive statistics and inferential statistics. The study found that there was a significant improvement from the vocabularies of eight grade students who treated by ESA method in SMP Negeri 9 Baubau.